PERAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI DAN KOMUNIKASI DI SEKOLAH DASAR - Darmansyah; Yanti Fitria; Suci Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Information and Communication Technology (ICT)-based learning media play a crucial role in Primary Schools (SD), enhancing student engagement through visual and interactive presentations. The research methodology employed in this study is literature review. Findings from the literature review indicate that the role of ICT-based learning media in designing learning through various packaging and dissemination of information facilitates teachers with the creation of diverse media. The use of simulation applications and educational games delivers material in an enjoyable and profound manner. Online platforms facilitate independent and collaborative learning, while technology aids in formative assessment and personalization. ICT-based learning media also support the development of ICT skills, open up global access, and enhance administrative efficiency in schools. This article provides a brief overview of the pivotal role of ICT-based learning media in advancing primary school education.